2020
DOI: 10.3390/s20030831
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Inertia and Optical Based Motion Capture during the VU-Return-to-Play- Field-Test

Abstract: The validity of an inertial sensor-based motion capture system (IMC) has not been examined within the demands of a sports-specific field movement test. This study examined the validity of an IMC during a field test (VU®) by comparing it to an optical marker-based motion capture system (MMC). Expected accuracy and precision benchmarks were computed by comparing the outcomes of a linear and functional joint fitting model within the MMC. The kinematics from the IMC in sagittal plane demonstrated correlations (r2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The precision of the IMU system was best in the shoulder (Figure 3), which is consistent with previous results in the literature [28,32]. The variability across subjects in the elbow DOF (Figure 2) for the IMU system was likely influenced by variations in sensor placement and movement artifacts from the sensor attachment method, which are known factors in the literature [39]. The variability across subjects in the neck and torso angles (Figures 4 and 5) appeared to be heavily task-influenced and the capture accuracy of the systems was likely affected by the varying motions used by the participants to achieve the task.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The precision of the IMU system was best in the shoulder (Figure 3), which is consistent with previous results in the literature [28,32]. The variability across subjects in the elbow DOF (Figure 2) for the IMU system was likely influenced by variations in sensor placement and movement artifacts from the sensor attachment method, which are known factors in the literature [39]. The variability across subjects in the neck and torso angles (Figures 4 and 5) appeared to be heavily task-influenced and the capture accuracy of the systems was likely affected by the varying motions used by the participants to achieve the task.…”
Section: Discussionsupporting
confidence: 88%
“…The Vicon optical marker-based system was selected as the reference system based on its popularity and usage in the literature [27,[36][37][38]44,45,48,[65][66][67][68]. The IMU-based [28][29][30][31][32][39][40][41][42][43][69][70][71] and markerless systems [13,[22][23][24][25]27,38,[44][45][46][47]72,73] were selected due to popularity in the literature and due to their differing mechanisms of motion capture. Please see Appendix B for diagrams of the sensor placements for the systems and the camera placements.…”
Section: Motion Analysis Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main finding of the present study was that the WIS motion capture system showed overall fair-to-excellent correlation with respect to the OMB system, and acceptable measurement errors in all the movements assessed. This finding confirmed the concurrent validity of the WIS system already underlined in previous studies [18,[28][29][30], and further extended its usability to clinical applications in the ACL rehabilitation context. For the first time, a stronger focus was put on clinically relevant biomechanical parameters used by the ACL professionals in the rehabilitation protocols after ACL injury in sport-specific, highspeed, and multidirectional movements.…”
Section: Discussionsupporting
confidence: 87%